Here comes Hortense! - Hartt-Sussman, Heather (Tundra Books, 2012)
A young boy is delighted when Nana and her new husband, Bob, ask him to join them at a theme park, but becomes disgusted when Bob's young granddaughter, Hortense, comes along and seems to hold all of Nana's attention.